An equivalent circuit model of li-ion battery based on electrochemical principles used in grid-connected energy storage applications - Li, Y.; Vilathgamuwa, D.; Farrell, T.; Choi, San Shing; Tran, N. (2017)
© 2017 IEEE. Based on basic electrochemical principles, an equivalent circuit model of a Li-ion battery is developed. The eventual aim of the work is to use such a model in the accurate control of power flow for a battery energy storage system (BESS) in grid-scale applications. The model developed here allows one to monitor the BESS internal states, by taking into consideration the internal dynamics of the battery including Li-ion concentration, overpotential and degradation. Comparison of the results obtained from the developed model with more established but computationally expensive models shows that the developed model performs well in terms of both external electrical characteristics and major internal chemical dynamics for the studies of grid-scale BESS.